Desarrollo de valor agregado en la auditoría de certificación en organizaciones de alta complejidad en Colombia con sistemas de gestión (2020)
Complexity is a concept found in different contexts; nevertheless, complexity is based on the recognition of its elements and the relationships between them. Understanding complexity in the organizational context is a precise objective to address when it comes to certification. Deepening in the existing variables within the organization’s dynamics will allow understanding the operation of its management systems for the generation of value from audits. This article highlights the research proposal of a model for certification audits in highly complex organizations in Colombia with management systems and describes how through its components it tends to generate value as a result of considering the particular characteristics of the organization, the levels of evolution and systems progress as well as the interaction of the various organizational elements, all explored in the research.